2021
DOI: 10.1093/hmg/ddab318
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-mediated degradation of keratins 7, 8, 17 and 18 by mutant KLHL24 in a foetal keratinocyte model: Novel insight in congenital skin defects and fragility of epidermolysis bullosa simplex with cardiomyopathy

Abstract: Epidermolysis bullosa simplex (EBS) with cardiomyopathy (EBS-KLHL24) is an EBS subtype caused by dominantly inherited, gain-of-function mutations in the gene encoding for the ubiquitin-ligase KLHL24, which addresses specific proteins to proteasomal degradation. EBS-KLHL24 patients are born with extensive denuded skin areas and skin fragility. Whilst skin fragility rapidly ameliorates, atrophy and scarring develop over time, accompanied by life-threatening cardiomyopathy. To date, pathogenetic mechanisms underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(128 reference statements)
1
4
0
Order By: Relevance
“…This result was in line with a reduced expression and phenotype of the explanted heart of one of the patients [101]. Meanwhile, another study reported that KLHL24 is also responsible for the turnover of foetal-like keratins 7,8,17 and 18 [103], while degradation of keratin 14 may be higher in foetal-like hiPSC-derived keratinocytes compared to adult keratinocytes [102]. These data would explain why patients develop congenital aplasia cutis but only mild skin fragility later in life.…”
Section: Klhl24 Variants Causing An Altered Klhl24 Proteinsupporting
confidence: 58%
See 1 more Smart Citation
“…This result was in line with a reduced expression and phenotype of the explanted heart of one of the patients [101]. Meanwhile, another study reported that KLHL24 is also responsible for the turnover of foetal-like keratins 7,8,17 and 18 [103], while degradation of keratin 14 may be higher in foetal-like hiPSC-derived keratinocytes compared to adult keratinocytes [102]. These data would explain why patients develop congenital aplasia cutis but only mild skin fragility later in life.…”
Section: Klhl24 Variants Causing An Altered Klhl24 Proteinsupporting
confidence: 58%
“…For instance, KLHL24 protein activity, whether through loss or gain of function, causes a strong dose-dependent phenotype in the heart, which seems directly related to expression of its target desmin [101,107]. The relationship to keratins in the skin is less straightforward and requires more cohesive data that may now be emerging with new studies [102][103][104]. Functional studies combined also suggest that the phenotype associated with DP reduction is both dose-and organ-dependent in nature, which is important knowledge for future interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis indicated that the monomers generated by SASPase cleavage are relatively stable, given their minor decrease in the N-terminal PSI, but a significant increase in the C-terminal PSI and a drop in GHI value; this likely permits their long-lasting functionality required for cross-linking of the proteins within the cornified envelope, and aggregation and collapse of the IF-based cytoskeleton. Intriguingly, the UPS system has been previously implicated in the degradation and turnover of keratins ( Yamazaki et al, 2012 ); increased keratin turnover is observed in a subtype of epidermolysis bullosa simplex (EBS) patients, resulting in shortened lifespan, replicative senescence, and decreased cellular resistance in keratinocytes ( Logli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis indicated that the monomers generated by SASPase cleavage are relatively stable, given their minor decrease in the Nterminal PSI, but a signi cant increase in the C-terminal PSI and a drop in GHI value; this likely permits their long-lasting functionality required for cross-linking of the proteins within the corni ed envelope, and aggregation and collapse of the IF-based cytoskeleton. Intriguingly, the UPS system has been previously implicated in the degradation and turnover of keratins 182 ; increased keratin turnover is observed in a subtype of epidermolysis bullosa simplex (EBS) patients, resulting in shortened lifespan, replicative senescence, and decreased cellular resistance in keratinocytes 183 .…”
Section: Discussionmentioning
confidence: 99%